BCAP promotes lupus-like disease and TLR-induced IFNα production in plasmacytoid dendritic cells - Chu, Talyn (My University, 2019)
Systemic lupus erythematosus (SLE) severity correlates with elevated serum levels of type I interferons (IFN), cytokines produced in large quantities by plasmacytoid dendritic cells (pDC) in response to engagement of TLR7 and TLR9 with endocytosed nucleic acids. B cell adaptor for PI3K (BCAP) promoted many aspects of TLR7-driven lupus-like disease including Isg15 and Ifit1 expression in blood and an immature pDC phenotype associated with higher IFN production. BCAP-/- mice produced significantly less serum IFNa than WT mice after injection of TLR9 agonist, and BCAP promoted TLR7 and TLR9-induced IFNa production specifically in pDC. TLR-induced IFNa production in pDC requires DOCK2-mediated activation of Rac1 leading to activation of IKKa, a mechanism we show was dependent on BCAP. BCAP-/- pDC had decreased actin polymerization, Rac1 activation, and reduced IKKa phosphorylation upon TLR9 stimulation. We show a novel role for BCAP in promoting TLR-induced IFNa production in pDC and in SLE pathogenesis.
Thesis (Ph.D.)--University of Washington, 2019
Keywords: BCAP; PI3K; Systemic Lupus Erythematosus; Type I IFN; Immunology; Immunology